Autohydrolysis pretreatment of Arundo donax: a comparison between microwave-assisted batch and fast heating rate flow-through reaction systems. Issue 1 (December 2015) - Galia, Alessandro; Schiavo, Benedetto; Antonetti, Claudia; Galletti, Anna; Interrante, Leonardo; Lessi, Marco; Scialdone, Onofrio; Valenti, Maria
Abstract Background Autohydrolysis of lignocellulosic biomass in liquid hot water has been widely studied owing to its high efficiency and relatively low cost. In the perspective of industrial applications, continuous or semi-continuous processes are more interesting than batch systems. Moreover, microwave heating of pretreatment systems has been proposed to intensify the kinetics of the process. In this study, the autohydrolysis of Arundo donax was performed in pure liquid hot water using a microwave-heated batch reactor and a semi-continuous flow-through reaction system with fast heating rate at the same operating conditions with the aim of performing a systematic comparison between the two different experimental apparatuses. Results The effect of process temperature and time, biomass to water mass to volume ratio and water flow rate on the concentration and yield of hydrolysis products was investigated. The flow-through set-up allowed us to reach biomass solubilization up to 44.5 wt% on dry basis, while the batch system stopped at 34.5 wt% suggesting that the mass transfer could be the rate-determining step in the solubilization of the constituting biopolymers. For example, in the flow-through layout, using a flow rate of 3.5 mL/min at 200 °C with 20 min of processing time, quantitative recovery of hemicellulose was obtained with limited formation of degradation products. Interestingly, higher cellulose/hemicellulose extraction ratios were found using the microwave-assisted batch reactor. FTIR analyses of the solid residues recovered after the pretreatment offered independent information on the fractions of liquefied biopolymers complementary to those derived from HPLC and UV–Vis spectroscopy. Conclusions Collected experimental results indicated that the flow-through system can be adopted to obtain complete solubilization of the hemicellulose fraction of Arundo donax addressing the product distribution in soluble compounds towards fermentable sugars with limited formation of sugar degradation products and with limited penalty in terms of dilution of the hydrolysate solution. It was also found that microwaves can promote cellulose depolymerization and solubilization, thus allowing a more comprehensive utilization of the biomass and that infrared spectroscopy can be a useful technique to estimate the effect of the pretreatment.